Analisis Yuridis Aspek Hukum Benda Tidak Bergerak Sebagai Objek Jaminan Fidusia - Hendri. S; Rusniati (Disiplin : Majalah Civitas Akademika Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2021)
The legal aspects of immovable objects as objects of fiduciary guarantees can be categorized into 3 (three) periods, namely: a. the period before Law no. 4 of 1996 concerning Mortgage Rights; b. period after the enactment of Law no. 4 of 1996 concerning Mortgage Rights, and: c. period after Law no. 42 of 1999 concerning Fiduciary Guarantees. The provisions regarding immovable objects here are to accommodate credit needs for building owners without land rights where this building has a high economic value in accordance with the principle of horizontal separation.